2015
DOI: 10.1093/medlaw/fwv028
|View full text |Cite
|
Sign up to set email alerts
|

Ethics, Embryos, and Evidence: A Look Back at Warnock

Abstract: SummaryThe Report of the Committee of Inquiry into Human Fertilisation and Embryology, the Warnock Report, forms the basis of the UK legislation on embryo research and its influence continues to be felt even though over thirty years have passed since its publication. The Warnock Committee was the first of its kind to consider how the advancements in human fertilisation and embryology should be regulated. This article examines the evidence submitted to the Warnock Committee, upon which its members ultimately re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 4 publications
0
20
0
Order By: Relevance
“…At that time, embryo research was the most debated matter concerning the ethics of IVF [13–15]. Two conflicting positions dominated the public debate: on the one hand, those of whom were outright against embryo research.…”
Section: The 14-day Limit and The Warnock Reportmentioning
confidence: 99%
See 4 more Smart Citations
“…At that time, embryo research was the most debated matter concerning the ethics of IVF [13–15]. Two conflicting positions dominated the public debate: on the one hand, those of whom were outright against embryo research.…”
Section: The 14-day Limit and The Warnock Reportmentioning
confidence: 99%
“…when sperm cells fertilise oocytes) and must be protected. Interestingly, not all the opponents of embryo research holding the view that embryos are persons were arguing from a religious standpoint [15]. Some of those arguing against embryo research in principle referred to the potentiality of the embryos to become fully developed persons and concluded that human life, no matter at what stage of development, should be granted full protection, and that embryos should not be used for research [16–18].…”
Section: The 14-day Limit and The Warnock Reportmentioning
confidence: 99%
See 3 more Smart Citations